Voices and Perspectives from Our Online Press on the State of English Language Teaching in Mexico - Sarracino, David Guadalupe Toledo; Landa, Laura García; Sánchez, Nahum Samperio; O’Grady, Darragh (Journal of Ecohumanism, 2024)
This documentary research on the discourse in electronic media surrounding the teaching and learning of English as a foreign language on the Mexico’s border describes the social framework and analyses various linguistic contexts to make provisional recommendations regarding foreign language policy in Mexico. The digital journalism selected issues an opinion on (1) the teaching of English as a language additional to Spanish in Mexico (English Language Teaching, ELT), and (2) Mexico’s position (at Federal and State level) implicit in their regional implementation of ELT. Thirteen articles from 12 regional, national, and international media sources were analysed using Guespin and Marcellesi’s (1986) and Arnoux and Bein’s (2015) theories, alongside Bardin’s (1996) content analysis method for linguistic contexts in border regions. Qualitative analysis techniques were employed to identify and categorize the positions on foreign language policy presented in the Mexican media. The authors conclude with recommendations for ELT policy, proposing actions for foreign language policy planning. We argue for raised teacher-training standards to improve foreign language learning in mainstream education and Private language schools, thus positioning the Universidad Autónoma de Baja California to take more agency in our regional support role to the Mexican Secretariate of Education